Strategies for Increasing GRDP Contribution to the Agricultural Sector in Banyuwangi District - Prapti, Kanthi Pangestuning (Budapest International Research and Critics University, 2021)
The economic distribution of Banyuwangi is almost one third of which is in the Agriculture, Forestry, and Fisheries categories. However, not all programs in the sub-sector can be implemented so that agricultural development based on the leading sub-sector is expected to be a priority. Therefore, strategic steps are needed in the development of the sub-sector in the future. The research method used is descriptive quantitative. The results showed: 1) The agricultural sector for food crops gave a very large contribution to Gross Regional Domestic Product (GRDP) every year with an average contribution for 5 years of 30.09%, followed by the fishery sub-sector with its contribution of 19.86%, livestock by 19.65%, plantations by 15.75%, horticulture by 9.94%, forestry and logging by 3.60% and agricultural and hunting services with a contribution of 1.11%; 2) The agricultural sector development strategy in increasing GRDP in Banyuwangi Regency that must be applied in this condition is to support an aggressive growth policy (growth oriented strategy).